Salvific, Ethical, and Consummative "Appearances" in the Pastoral Epistles? A Response to Rob van Houwelingen - Manomi, Dogara Ishaya 1985- (2019)
In his article titled "The Meaning of ἐπιϕάνεια in the Pastoral Epistles," Rob van Houwelingen argues and concludes that ἐπιϕάνεια is used in 1 Timothy and Titus, on the one hand, to refer to the second coming of Christ, while it is used in 2 Timothy, on the other hand, to refer to the first coming of Christ. He further argues that the testamentary nature of 2 Timothy, unlike 1 Timothy and Titus, accounts for Paul's focus on the first epiphany of Christ therein. While van Houwelingen's article title and conclusion suggest an analysis that encompasses comprehensive lexical and conceptual elements, he, however, undertakes only a lexical study of the noun cognate ἐπιϕάνεια, without justifying the exclusion of the verbal (and other) cognates. In response, this article undertakes a comprehensive analysis of all the cognates and concepts of ἐπιϕάνεια in the Pastoral Epistles, focusing on their salvific, ethical, and consummative dimensions. It concludes that, in each of the three letters, depending on the context, ἐπιϕάνεια as a concept is used both in reference to the first and second comings of Christ. The emphasis is, however, more on the first than the second epiphany. Moreover, both epiphanies share an ethical significance that connects them together.
Keywords: Christ; Pastoral Epistles (PE); ἐπιϕάνεια; Appearance; van Houwelingen